HUMAN RESOURCES' ROLE IN BUILDING EMPLOYEE ENGAGEMENT IN GENERATION Z - Rahmi Yuningsih Puteri (RADJA PUBLIKA, 2025)
This study aims to analyze the role of Human Resources (HR) in building employee engagement among Generation Z, who are beginning to dominate the workforce. The focus of this study is on how HR transforms from an administrative function to a strategic role that is more adaptive to the needs of the new generation. The research method used is a literature study by reviewing various literature, journals, scientific articles, and research reports related to HR, employee engagement, and the characteristics of Generation Z. The results of the study indicate that employee engagement is an important factor in improving organizational performance and sustainability, where employee engagement is influenced by individual aspects such as intrinsic motivation and the need for recognition, as well as organizational aspects such as supportive leadership, open communication, reward systems, and a positive work environment. Generation Z, with its characteristics that value flexibility, work-life balance, and openness to technology, demands a more innovative and humanistic HR management strategy. Therefore, HR is required to create a meaningful, inclusive work environment, and provide space for creativity and self-development, so that engagement can be formed optimally and the organization is able to maintain its competitiveness in the modern era.